Forced Convection Around a Solid Cylinder - MOHD YUSOFF, NUR AZIZI HILMAN; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2025)
Forced convection heat transfer is essential in engineering applications, offering insights into optimizing thermal systems for efficiency and reliability. This study focuses on analysing forced convection around a solid cylinder using COMSOL Multiphysics software. Dimensional equations were transformed into dimensionless forms to facilitate simulation. Results revealed significant changes in streamline and velocity patterns as Reynolds numbers varied (Re = 1, 10, 20, 40), demonstrating the transition from laminar to complex flow dynamics and its impact on heat transfer. This work highlights the potential of COMSOL Multiphysics for studying thermal phenomena and proposes further research on complex geometries and varied parameters.